Evaluating Firefighters' Joint Mobility and Muscular Activity during Load Carriage (Journal of Fiber Bioengineering and Informatics, 2023)
This study aimed to quantify the firefighters' joint mobility and muscular activity during self-contained breathing apparatus (SCBA) carriage and evaluate the effectiveness of shoulder strap length variation. Three varying-strapped SCBAs and a control condition with no SCBA equipped were evaluated. Joint range of motion (ROM) and surface electromyography (sEMG) signals were synchronously collected when twelve male subjects walked in four test samples. Results showed that carrying SCBA had more pronounced impacts on the joint ROM and sEMG around the proximal torso, suggesting that the training of firefighters focuses on the coordinated movement of muscles and joints in the trunk. The length of the SCBA strap was suggested to be set at 98-105 cm for firefighters who are 172-178 cm.